Sand Supplier Selection Analysis Based on the Integration of Analytical Hierarchy Process (AHP) and Taguchi Quality Loss Function Methods: Analisa Pemilihan Supplier Pasir Berdasarkan Integrasi Metode Analytical Hierarchy Process (AHP) dan Taguchi Quality Loss Function - Sofillauny, Zahara; Wahyuni, Hana Catur; Sukmono, Tedjo; Putra, Boy Isma (Universitas Muhammadiyah Sidoarjo, 2023)
Supplier selection process is a step to evaluate and select the most suitable supplier to see the needs of the company or organization. This evaluation is important to ensure that the selected supplier is able to provide quality products or services, competitive prices, timely delivery, and meet ethical and sustainability standards. This research uses two methods, namely Analytical Hierarchy Process (AHP) and Taguchi Loss Function. AHP is used to calculate the weight of criteria, while the Taguchi Loss Function is used to estimate losses caused by suppliers. The criteria applied in supplier evaluation are quality criteria, product accuracy, delivery, price, warranty policy, and response to claims. The results obtained from this study PT. Bumi Makmur with a percentage loss of 21%, while the supplier that has the largest loss value is PT. Mergo Bopo with a percentage of 47%. Highlights : Integration of AHP and Taguchi Loss Function enhances supplier selection accuracy. Identified supplier exhibits substantial loss percentage, emphasizing the importance of thorough evaluation. Findings enable informed decision-making, facilitating risk mitigation and operational optimization Keywords :Supplier Evaluation; Sand; Analytical Hierarchy Process, Taguchi Loss Function